Relationship between self control and academic procrastination in completing thesis - Roni Ariyanto; Netrawati Netrawati; Yusri Yusri (Jurnal Neo Konseling, 2019)
This study aims to: (1) Describe student academic procrastination, (2) Describe student self control, and (3) Test the relationship of self control and academic procrastination in completing thesis. The research subjects were 120 students, using instruments with Likert scale models. The percentage analysis technique and to test the relationship of the data were analyzed using the Pearson Correlation Product Moment statistical formula with the help of the SPSS for Windows version 20.0 program. The results of the study revealed that: (1) the level of academic procrastination in completing the thesis was classified as moderate, (2) the level of student self control in completing the thesis was classified as moderate, and (3) there was a significant positive relationship between self control and academic procrastination in completing the thesis with significance level 0,000, r count 0.566, and r table 0.178.